Bolidophyceae, a Sister Picoplanktonic Group of Diatoms – A Review - Kuwata, Akira; Yamada, Kazumasa; Ichinomiya, Mutsuo; Yoshikawa, Shinya; Tragin, Margot; Vaulot, Daniel; Lopes dos Santos, Adriana (Frontiers in Marine Science, 2018)
Pico- and nano-phytoplankton (respectively, 0.2-2 and 2-20 µm in cell size) play a key role in many marine ecosystems. In this size range, Bolidophyceae is a group of eukaryotes that contains species with cells surrounded by 5 or 8 silica plates (Parmales) as well as naked flagellated species (formerly Bolidomonadales). Bolidophyceae share a common ancestor with diatoms, one of the most successful groups of phytoplankton. This review summarizes the current information on taxonomy, phylogeny, ecology and physiology obtained by recent studies using a range of approaches including metabarcoding. Despite their rather small contribution to the phytoplankton communities (on average less than 0.1%), Bolidophyceae are very widespread throughout marine systems from the tropics to the pole. This review concludes by discussing similarities and differences between Bolidophyceae and diatoms.